2018
DOI: 10.21037/tau.2017.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Low dose rate prostate brachytherapy

Abstract: Low dose rate (LDR) prostate brachytherapy is an evidence based radiation technique with excellent oncologic outcomes. By utilizing direct image guidance for radioactive source placement, LDR brachytherapy provides superior radiation dose escalation and conformality compared to external beam radiation therapy (EBRT). With this level of precision, late grade 3 or 4 genitourinary or gastrointestinal toxicity rates are typically between 1% and 4%. Furthermore, when performed as a same day surgical procedure, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 126 publications
(120 reference statements)
0
28
0
Order By: Relevance
“…The International Commission on Radiologic Units and Measurements defines HDR as a dose delivered at a rate >12 Gy/h, although in actuality this is usually much higher, often in excess of 1 Gy per minute (7,12). With regards to radiation biology, the degree of dose escalation achievable with HDR brachytherapy, compared to other EBRT techniques and LDR, may be more effective in killing prostate cancer cells (7,20,21). The rapid dose delivery seen in HDR is considered to be selectively more damaging to cells with lower alpha/beta ratios, such as prostate cancer and late responding normal tissues (22)(23)(24).…”
Section: Hdr Boostmentioning
confidence: 99%
“…The International Commission on Radiologic Units and Measurements defines HDR as a dose delivered at a rate >12 Gy/h, although in actuality this is usually much higher, often in excess of 1 Gy per minute (7,12). With regards to radiation biology, the degree of dose escalation achievable with HDR brachytherapy, compared to other EBRT techniques and LDR, may be more effective in killing prostate cancer cells (7,20,21). The rapid dose delivery seen in HDR is considered to be selectively more damaging to cells with lower alpha/beta ratios, such as prostate cancer and late responding normal tissues (22)(23)(24).…”
Section: Hdr Boostmentioning
confidence: 99%
“…Different brachytherapy sources with own design have been studied utilizing Monte Carlo (MC) simulation and experimentally by different dosimeters [1][2][3][4][5][6][7]. Among the sources, 125 I seed also has designed and used to cancerous tissue treatment [8][9][10][11][12]. Villagas et al [9] conducted a study to characterize the magnitude of the spread in specific energy deposition per cell and reported increasing in micro-dosimetric value with decreasing target size and decreasing energy of the radiation quality.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sources, 125 I seed also has designed and used to cancerous tissue treatment [8][9][10][11][12]. Villagas et al [9] conducted a study to characterize the magnitude of the spread in specific energy deposition per cell and reported increasing in micro-dosimetric value with decreasing target size and decreasing energy of the radiation quality. They also reported that in clinical relevant dose the maximum spread dose 6% for 125 I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For brachytherapy, radioisotopes with energy <50 keV, such as 125 I and 103 Pd sources [7-9] with typical implants of 50-80 metallic seeds encasing isotopes, are used as low dose rate (LDR) [10] therapies for the treatment of prostate cancer, uveal melanomas and brain tumours. The dose is estimated by a number of computer codes such as EGSnrc, GEANT [11], PENELOPE [12] and MCNP [13] based on Monte Carlo (MC) methods [14].…”
Section: Introductionmentioning
confidence: 99%